The Effectiveness of Online Learning in Speaking Course - Novita Al Ihyak Dieni; Widiarsih Mahanani (Universitas Muhammadiyah Kalimantan Timur, 2022)
Online learning must be done by educators in distance learning during the handling Covid-19. Mastery of English skills that require direct practice must also be through online learning, for example, mastery of speaking skill by undergraduate students of English Study Program in Universitas 17 Agustus 1945 (Untag) Semarang. From pre-observation data, there were many students who feel insecure, nervous, and embarrassed when practicing speaking. This is what causes students to be less maximal in mastering speaking skill. The purpose of this study was to identify the effectiveness of online learning, focusing on using Google Classroom and Microsoft (MS) Teams in Speaking Course at the first semester students of English Study Program in Untag Semarang. So that researchers used experimental method. In data collection, researchers used a speaking test which was then analyzed using t-test formula. The data analyzed were the results of pre-tests and post-tests from two groups, namely experimental group and control group. From the results of the statistical analysis of t-test on the pre-test value, t count (1.04) < t table (1.7), it means that Ho is accepted and Ha is rejected. From the results of the statistical analysis of t-test on post-test values, t count (1.5) < t table (1.76), it means that Ho is accepted and Ha is rejected. From the results of statistical analysis of hypothesis tests, it can be concluded that there is no difference grades in Speaking Course between students taught using Google Classroom and students taught using Ms. Teams.